Peanut agglutinin specifically binds to a sperm region between the nucleus and mitochondria in tunicates and sea urchins. Issue 6 (17th April 2018) - Nakazawa, Shiori; Shirae‐Kurabayashi, Maki; Sawada, Hitoshi
Abstract : Peanut agglutinin (PNA) is an established marker of the mammalian acrosome. However, we observed that PNA specifically binds to a unique intracellular structure alongside the nucleus in ascidian sperm. Here, we characterize the PNA‐binding structure in sperm of marine invertebrates. PNA bound to the region between the mitochondrion and nucleus in spermatozoa of ascidians, sea urchins, and an appendicularian. However, PNA‐binding substances were not exposed by the calcium ionophore ionomycin in three ascidian species, indicating that it is a distinct structure from the acrosome. Instead, the ascidian PNA‐binding region was shed with the mitochondrion from the sperm head via an ionomycin‐induced sperm reaction. The ascidian PNA‐binding substance appeared to be solubilized with SDS, but not Triton X–100, describing its detergent resistance. Lectins, PHA‐L4, SSA, and MAL‐I were detected at an area similar to the PNA‐binding region, suggesting that it contains a variety of glycans. The location and some of the components of the PNA‐binding region were similar to known endoplasmic reticulum (ER)‐derived structures, although the ER marker concanavalin A accumulated at an area adjacent to but not overlapping the PNA‐binding region. Therefore, we conclude that ascidian sperm possess a non‐acrosomal, Triton‐resistant, glycan‐rich intracellular structure that may play a general role in reproduction of tunicates and sea urchins given its presence across a wide taxonomic range.